Biofuels production: A sustainable solution to combat climate change - PRASAD, S; KUMAR, AMIT; MURALIKRISHNA, K S (The Indian Journal of Agricultural Sciences, 2014)
This paper reviews the situation of biofuels production with regard to climate change and sustainability. The biomass energy or biofuels combustion is carbon neutral or even carbon negative as the carbon, which is stored during its growth, is released and does not add new carbon to the active carbon cycle, whereas fossil fuels such as coal, oil and natural gas remove carbon from geologic storage and contribute to climate change by emission of GHGs. Biofuel also controls the carbon emissions from biomass facilities which would have been released back into the atmosphere through natural decay or disposal through open-burning. Inspite of these GHG benefits, the progress in biofuels expansion is at crossroads as it is influenced by various factors like land use changes and food security related issues. However biofuels from degraded land and from non-food crops are promising and will help in climate change mitigation. Proper planning in land use and identifying most appropriate policies for promoting this will help in tackling the global issue and in achieving the goal. The technology utilizing carbon sequestered in various sources, for ethanol, biodiesel and other biofuels production is a sustainable solution to climate change rather than biofuels from food crops.